Probes for the heterogeneity of muscimol binding sites in rat brain - Müller, Veronika; Ernst, Margot; Baykuchkarova, Aygul; Koniuszewski, Filip; Bampali, Konstantina; Seidel, Thomas; Scholze, Petra (Frontiers in Pharmacology, 2024)
Introduction: The plant-based alkaloid muscimol is a potent agonist of inhibitory GABAA-neurotransmitter receptors. GABAA receptors are a heterogeneous family of pentameric complexes, with 5 out of 19 subunits assembling around the central anion pore. Muscimol is considered to bind to all receptor subtypes at the orthosteric drug binding site at the β+/α− interface. Recently, we observed that the antipsychotic drugs clozapine (CLZ), loxapine (LOX) and chlorpromazine (CPZ) although exerting functional inhibition on multiple GABAA receptor subtypes showed diverging results in displacing 3H-muscimol. While a complete displacement could be observed in hippocampal membranes by bicuculline (BIC), and no displacement with CPZ, the compounds CLZ and LOX competed partially. Non-sigmoidal, complex dose response curves were indicative of multiple sites. In the current study we now aimed to investigate more extensively this heterogeneity of bicuculline sensitive muscimol sites in rat brain. Methods: We tested membranes from four different brain regions (hippocampus, cerebellum, thalamus and striatum) and selected recombinantly expressed subunit combinations with displacement assays. 3H-muscimol displacement was tested with BIC, LOX, CLZ and CPZ. In silico ligand structural analysis and computational docking was performed. Results: We observed a unique pharmacology of each tested compound in the studied brain regions. Combining two of the tested ligands suggests that in striatum all CLZ sites are contained in the pool of LOX sites, while the CPZ sites may in part be non-overlapping with LOX sites. Experiments on recombinantly expressed receptors indicate, that BIC can displace 3H-muscimol from all tested receptors, while LOX and CLZ display different and variable competition indicative of multiple sites. Molecular docking produced structural correlates of the observed diversity of muscimol sites on the basis of bicuculline bound experimental structures. Discussion: These findings indicate that 3H-muscimol binding sites in rat brain are heterogeneous, with different populations of receptors, which are CPZ, LOX or CLZ sensitive or insensitive. These binding sites show a varying distribution in different rat brain regions. Molecular docking suggests that the so-called loop F region of α subunits drives the observed differences.